العلاقة بين المفاهيم الإسلامية لقيم المواطنة والمسؤولية الاجتماعية والأمن الفكري لدى طلاب المرحلة الثانوية بمنطقة حائل السعودية: The Relationship between Islamic Concepts of the Values of Citizenship, Social Responsibility and Intellectual Security among Secondary School Students of Hail, Saudi Arabia - Alshammari, Ateeq; Bin Ismail, Zawawi; Ismail, Wail Muin; Bin Sulaiman, Abdul Muhsien (Journal of Islamic Educational Research, 2022)
This study aimed at diagnosing the reality of Islamic concepts of citizenship values; social responsibility and intellectual security among secondary school students in Hail at Saudi Arabia, and studying the correlation between these concepts, the research depended on the descriptive correlational approach, and principal sample contained (400) male and female students, the research finding representing the most important, the availability of values among secondary school students at an average level, and the value of obedience was the highest level, while the value of participation was the weakest value and abundance While social responsibility was at a high rate in general, social responsibility towards oneself was the highest level, while responsibility towards society was the lowest. In terms of intellectual security, it was generally high, and the value role dimension was the highest level. The research also showed that there is a positive correlation between the three concepts, so the correlation was strong between the citizenship values and social responsibility, as well as between the citizenship values and intellectual security, and also the strong correlation between social responsibility and intellectual security.